Correlation of losses from evaporation and quality motor spirit - Бойченко, С.В.; Іванов, С.В.; Федорович, Л.А.; Черняк, Л.М. (Proceedings of National Aviation University (archive), 2004)
The paper is devoted to correlation of losses from evaporation and quality motor spirit. The results of researches contemporary motor spirit are presented. Is established, that the evaporation results in increase in structure of petrol of concentration high-molecular hydrocarbon, which at excess of allowable concentration negatively influence quality and operational properties of motor spirit.